2021
DOI: 10.1029/2020sw002639
|View full text |Cite
|
Sign up to set email alerts
|

Data‐Driven Forecasting of Low‐Latitude Ionospheric Total Electron Content Using the Random Forest and LSTM Machine Learning Methods

Abstract: The random forest and LSTM methods are employed, the data sources are space 13 measurements characterizing the solar-terrestrial environment 14• Variable importance ranking showed that F10.7, Lyman alpha are top predictors 15 agreeing well with the physics of ionospheric formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Results of the model established for station HRBN showed that the RMSE of the ED-LSTME model was 1.455 TECU, which is obviously larger than the RMSEs of the bi-LSTM model for the 1 hr (0.743 TECU) and 2 hr (0.998 TECU) ahead predictions tested in this study. Zewdie et al (2021) applied an LSTM method to predict the TEC at an equatorial GPS station up to 5 hr ahead, with a 30-min interval, and results indicated that the correlation coefficient decreased while the RMSE increased as the time of the prediction is further into the future. Moreover Finally, the new model captures the variations of the ionosphere TEC under geomagnetic storm conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results of the model established for station HRBN showed that the RMSE of the ED-LSTME model was 1.455 TECU, which is obviously larger than the RMSEs of the bi-LSTM model for the 1 hr (0.743 TECU) and 2 hr (0.998 TECU) ahead predictions tested in this study. Zewdie et al (2021) applied an LSTM method to predict the TEC at an equatorial GPS station up to 5 hr ahead, with a 30-min interval, and results indicated that the correlation coefficient decreased while the RMSE increased as the time of the prediction is further into the future. Moreover Finally, the new model captures the variations of the ionosphere TEC under geomagnetic storm conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zewdie et al. (2021) applied an LSTM method to predict the TEC at an equatorial GPS station up to 5 hr ahead, with a 30‐min interval, and results indicated that the correlation coefficient decreased while the RMSE increased as the time of the prediction is further into the future. Moreover, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, such processing methods theoretically introduce more model errors and some original ionospheric information is lost in the forecast stage. Secondly, because of the continuous forecast, the error accumulation phenomenon occurs as the forecast hour increases within a day (Ruwali et al, 2021;Zewdie et al, 2021). Many studies have been done on the variation characteristics of the ionosphere, showing that the ionosphere mainly presents periodic regular variation patterns such as 11-year cycle variation, seasonal variation and diurnal variation.…”
Section: Introductionmentioning
confidence: 99%